MONITORING PERUBAHAN SUHU IBU KOTA NEGARA TAHUN 1993-2019 MENGGUNAKAN CITRA SATELIT LANDSAT (Studi Kasus: Jakarta, Singapura, Kuala Lumpur Dan Bangkok) - Rasyidi, Emil Salim; Sandi, Reski; Buraerah, Muhammad Fikruddin (Lembaga Penelitian dan Pengabdian pada Masyarakat Universitas Bosowa, 2020)
Developments in the Capital territory of a State that is dynamic often creates an impact on the temperature of an area in the urban, it is based on the high demand of the population living in urban areas in terms of both facilities and infrastructure resulted in an urban space less support for the occurrence of such development. Increasing temperatures in urban areas provide a lot of negative effects, such is the potential for fires, air pollution up to comfort of live in the state capital. And the others problems, with the global warming which occurred in the world, such as the melting of ice on most of the north pole, unpredictable Global warming and the number of flora and fauna habitat damaged. Therefore, researchers feel the need for monitoring changes in surface temperature in the Capital City of the South-East Asia, namely Jakarta, Singapura, Kuala Lumpur and Bangkok from years 1993 -2019, Monitoring changes in surface temperature in the capital city of the State carried out using Landsat 4, Landsat 7 TM, and Landsat 8 OLI with thermal band resolution of 90m, the aim of this study is Monitoring and analysis of Surface Temperature changes in Southeast Asia Capital City form 1993-2019. the result in this research is Surface Temperature changes map of the capital city of Southeast Asia Capital City form 1993-2019 case study: Jakarta, Singapura, Kuala Lumpur and Bangkok from years 1993-2019